2016
DOI: 10.1371/journal.pone.0154735
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness, Costs and Coastal Protection Benefits of Natural and Nature-Based Defences

Abstract: There is great interest in the restoration and conservation of coastal habitats for protection from flooding and erosion. This is evidenced by the growing number of analyses and reviews of the effectiveness of habitats as natural defences and increasing funding world-wide for nature-based defences–i.e. restoration projects aimed at coastal protection; yet, there is no synthetic information on what kinds of projects are effective and cost effective for this purpose. This paper addresses two issues critical for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
305
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 470 publications
(309 citation statements)
references
References 41 publications
1
305
0
3
Order By: Relevance
“…Aboveground vegetation also effectively attenuates waves, reduces surge height and decreases the area that is inundated (Augustin et al, 2009;Wamsley et al, 2010;Pinsky et al, 2013; Möller et al, 2014;Narayan et al, 2016). It has been observed that both deposition and erosion occur due to vegetation during hurricane events (Yang et al, 2003;Fan et al, 2006;Howes et al, 2010).…”
Section: Aboveground Vegetationmentioning
confidence: 99%
“…Aboveground vegetation also effectively attenuates waves, reduces surge height and decreases the area that is inundated (Augustin et al, 2009;Wamsley et al, 2010;Pinsky et al, 2013; Möller et al, 2014;Narayan et al, 2016). It has been observed that both deposition and erosion occur due to vegetation during hurricane events (Yang et al, 2003;Fan et al, 2006;Howes et al, 2010).…”
Section: Aboveground Vegetationmentioning
confidence: 99%
“…Awareness of the role of mangroves in coastal protection has led to large-scale programs to rehabilitate and replant mangroves in countries like Vietnam and the Philippines as well as small programs in many other countries. A review of 53 nature-based defense projects (including 12 mangrove projects) found that mangroves could be 2-6 times less expensive than the commonly used alternative, submerged breakwaters, for relatively low waves (Narayan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Natural coastal infrastructure, including beaches, dunes, oyster and coral reefs, seagrass beds, and marshes, can reduce wave energy, coastal erosion, and flood hazards [14,17,[25][26][27][28]. For example, insurance industry models estimate that wetlands have saved more than $625 million in avoided flooding damages and that communities behind marshes experienced 20% less property loss during Hurricane Sandy [29].…”
Section: Building Better Coastal Infrastructurementioning
confidence: 99%